If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 12 + -1(12x + 18) = -2x + 36 Reorder the terms: 3x + 12 + -1(18 + 12x) = -2x + 36 3x + 12 + (18 * -1 + 12x * -1) = -2x + 36 3x + 12 + (-18 + -12x) = -2x + 36 Reorder the terms: 12 + -18 + 3x + -12x = -2x + 36 Combine like terms: 12 + -18 = -6 -6 + 3x + -12x = -2x + 36 Combine like terms: 3x + -12x = -9x -6 + -9x = -2x + 36 Reorder the terms: -6 + -9x = 36 + -2x Solving -6 + -9x = 36 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. -6 + -9x + 2x = 36 + -2x + 2x Combine like terms: -9x + 2x = -7x -6 + -7x = 36 + -2x + 2x Combine like terms: -2x + 2x = 0 -6 + -7x = 36 + 0 -6 + -7x = 36 Add '6' to each side of the equation. -6 + 6 + -7x = 36 + 6 Combine like terms: -6 + 6 = 0 0 + -7x = 36 + 6 -7x = 36 + 6 Combine like terms: 36 + 6 = 42 -7x = 42 Divide each side by '-7'. x = -6 Simplifying x = -6
| 2(r+5)=10+4(r+6) | | x^2-64x+584=0 | | 8(3m+4)=2m-4 | | 2.4=(12+3m) | | 126x^3-3x+3-1=0 | | x^2-6x+y^2-2y-8=0 | | f(x)=2x^3-9x^2+12x-3 | | cotx=0.5 | | a+1.35=2a-1 | | x+2*5=6x | | (18-x)(12-x)=112 | | 2x(3y+7)= | | 1.8+7n=9.54n | | 7x^2+-2=6x^2-6x-9 | | 8x^9+7x^3=5 | | r+r+8=16 | | 0.5x-0.3(5-x)=2.1 | | 7b+7c-(8a*78d)= | | g(x)=(x^2-3x-4)(x^2-1) | | 13g=7g+54 | | 7n+8=(-20) | | 7n+8=6 | | k=9k+28 | | 8y-14z=7 | | 8y-13z=7 | | 6y-13z=7 | | 4xy+5y=3x-2 | | 6-6x-4=-3+3x-13 | | 2x=10y-20 | | x^2-10*x-81=0 | | 2x=-8y+34 | | 6k+5k=11 |